Molekulare Tumortherapie: Phase-I/II-Netzwerkstruktur der Gesellschaft für Pädiatrische Onkologie und Hämatologie - Nesper-Brock, Martina; Metzler, Markus; Wotschofsky, Zofia; Reinhardt, Dirk; Fischer, Matthias; Rutkowski, Stefan; Kratz, Christian; Thorwarth, Anne; Graf Einsiedel, Hagen; Schrappe, Martin; Mauz-Körholz, Christine; Witt, Olaf (Onkologe, 2021)
Background: To enable the rapid and efficient implementation of early clinical trials for pediatric patients and provide comprehensive access to novel treatment options for pediatric relapse or high-risk patients, five regional phase I/II trial networks have been established under the auspices of the Society for Pediatric Oncology and Hematology (GPOH). The network structure secures, bundles and organizes required competencies and resources and has established processes to optimize operational trial efficiency. The INFORM study is a population-based molecular diagnostic study for children and adolescents with recurrent cancer in Germany and 11 other countries. Preliminary data show that precision medicine in pediatric oncology is possible in an international multicenter setting, provides clinical benefit for subgroups of patients and helps to identify hereditary predispositions, to refine diagnoses and to match patients in suitable phase I/II clinical trials. Conclusions: The portfolio of innovative biomarker driven phase I/II clinical trials for children and adolescents with recurrent tumor diseases in Germany is currently limited. Therefore, the development of innovative, targeted therapy concepts and combination therapies is an important task in the coming years.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Clinical trial; phase I as topic; Clinical trial; phase II as topic; Molecular diagnostic techniques; Molecular targeted therapy; Precision medicine